2013
DOI: 10.4322/polimeros.2014.008
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan microspheres applied for removal of oil from produced water in the oil industry

Abstract: Abstract:The discharge of oily wastewaters in the environment is steadily increasing, causing serious damages. Among various treatment methods, adsorption is generally considered the most appropriate, since it can remove both organic and inorganic pollutants. Adsorption using low-cost alternative biopolymers for removal of contaminants from wastewater has been widely investigated. In this context, chitosan has been drawing particular attention because, among its many applications, it can be used in the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 14 publications
0
15
0
3
Order By: Relevance
“…When applying pH-responsive polymers, the polysaccharides are preferred in many applications, because they join pH-sensitiveness with inherent biological properties. One of the most outstanding pH-sensitive biopolymer is chitosan [98,99] , a polysaccharide which naturally occurs in certain fungi [100] , but is extensively obtained by the deacetylation of chitin [58,101,102] , which is extracted from the shells of crustaceans, from the exoskeleton of many arthropods and from some fungi [103] . Despite the massive annual production and easy availability, due to its poor solubility in almost all common solvents, chitin does not find practical applications, except for being a source for obtaining chitosan [102][103][104][105] .…”
Section: Ph-sensitive Polymersmentioning
confidence: 99%
“…When applying pH-responsive polymers, the polysaccharides are preferred in many applications, because they join pH-sensitiveness with inherent biological properties. One of the most outstanding pH-sensitive biopolymer is chitosan [98,99] , a polysaccharide which naturally occurs in certain fungi [100] , but is extensively obtained by the deacetylation of chitin [58,101,102] , which is extracted from the shells of crustaceans, from the exoskeleton of many arthropods and from some fungi [103] . Despite the massive annual production and easy availability, due to its poor solubility in almost all common solvents, chitin does not find practical applications, except for being a source for obtaining chitosan [102][103][104][105] .…”
Section: Ph-sensitive Polymersmentioning
confidence: 99%
“…Considering the results of characterization analyses and MDO removal tests, the ultrasound treatment has increased the available surface area of UT-β-chitin, which resulted in a significant improvement of its MDO removal performance compared with its source material (β-chitin). Reports on other sorbents also detected a direct relationship between increase in available surface area and enhancement in oil removal (Ahmad et al 2004(Ahmad et al , 2005aSrinivasan and Viraraghavan 2010;Farias et al 2015;Grem et al 2013).…”
Section: Removal Of Marine Diesel Oilmentioning
confidence: 86%
“…Many authors attribute its competence to the positive character of its amino groups, that could either neutralize negatively charged oils (Ahmad et al 2004(Ahmad et al , 2005aSrinivasan and Viraraghavan 2010;Sokker et al 2011;Barros et al 2014) as attract slightly polar molecules present in fossil fuels (Grem et al 2013;Ferreira et al 2009). The cyclic conformation of carbons in the main chain of chitosan would also be responsible for a low polarity that could attract hydrocarbon compounds through Van der Waals interactions (Grem et al 2013). In this sense, chitosan was the sorbent with the highest expectations, and the reasons behind such results are important to stand out.…”
Section: Removal Of Marine Diesel Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…Grem and co-authors reported that chitosan microspheres produced by ionic gelation of chitosan with sodium tripolyphosphate (STP) were able to separate 90% of the oil from produced water containing 200 ppm oil suspension using packed columns [64].…”
Section: Chitosan-based Materials For the Removal Of Oil Pollution Frmentioning
confidence: 99%